Superassembly of Porous Fetet(NiFe)octO Frameworks with Stable Octahedron and Multistage Structure for Superior Lithium–Oxygen Batteries. Issue 21 (6th April 2020) - He, Biao; Wang, Jun; Liu, Jiaqing; Li, Yong; Huang, Qishun; Hou, Yue; Li, Gaoyang; Li, Jiajia; Zhang, Runhao; Zhou, Junjie; Tian, Wei; Du, Yong; et al.
Abstract: Promising lithium–oxygen batteries (LOBs) with extra‐high capacities have attracted increasing attention for use in future electric devices. However, the challenges facing this complicated battery system still limit their practical applications. These challenges mainly consist of inefficient product evolution and low‐activity catalysts. In present work, a cation occupying, modified 3D‐architecture NiFeO cubic spinel is constructed via superassembly strategy to achieve a high rate, stable electrocatalyst for LOBs. The octahedron predominant spinel provides a stable polycrystal structure and optimized electronic structure, which dominates the discharge/charge products evolution with multiformation kinetics of crystal Li2 O2 and Li2− x O2 at low and high rate conditions and energetically favors the mass transport between the electrode/electrolyte interface. Simultaneously, the porous NiFeO framework provides adequate spaces for Li2 O2 accommodation and complex channels for sufficient electrolyte, oxygen, and ion transportation, which dramatically alter the cathode catalysis for an unprecedented performance. As a consequence, a large specific capacity of 23413 mAh g −1 and an excellent cyclability of 193 cycles at a high current of 1000 mA g −1, and 300 cycles at a current of 500 mA g −1, are achieved. The present work provides intrinsic insights into designing high‐performance metal oxide electrocatalysts for Li–O2 batteries with fine‐tuned electronic and frame structure. Abstract : A well‐designed porous NiFeO framework with octahedron‐predominant discharge product evolution, for superior long life and a high performance lithium–oxygen batteries is presented. These findings provide insight into the development of spinel oxides as an electrocatalyst for longer lifespan energy storage.